Evaluation of a school-based self-esteem intervention program for adolescents (Dhaka University Journal of Biological Sciences, 2021)
The researchers aimed to evaluate a school-based self-esteem intervention program. The program's focus was to implement a culturally appropriate selfesteem intervention tool for school-going adolescents through selfhood, affiliation, competence, mission, and security activities. This study randomly recruited 183 nine-grade students aged 13 - 16 years. A pre-post design and two distinct measures were utilized to measure the intervention's social efficacy validity. The target skills' specific measures (Self-esteem, self-concept, selfconfidence) and effect measures (nature of friend connections, the suitability of intervention for youths) were introduced. Comparisons of scores using ANOVA's and t-tests discovered that the intervention had the most substantial effect on girls' self-confidence (p = 0.001) and changes in the self-concept, disruptive behavior, self-confidence, and social competence. The study's results provided satisfactory evidence of intervention effectiveness, and the post-test result showed little change across the study period.Dhaka Univ. J. Biol. Sci. 30(2): 197-205, 2021 (July)